Metode Metode Benteng-bentengan Berbasis Media Interaktif untuk Meningkatkan Motivvasi dan Kolaborasi Siswa: Studi Pengembangan Pada Pembelajaran IPS di SMP Negeri 51 Surabaya - Laily Nadhiroh (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2026)
Learning is an important component in the educational process, so innovative methods are needed that can address the problem of low student motivation and collaboration in the classroom. This study focuses on the development of the Benteng-bentengan method based on interactive media as an alternative social studies learning strategy. The purpose of this study was to determine the level of validity, practicality, and effectiveness of the resulting method. The study used the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Product validity was obtained through expert testing, namely validation by material experts with a percentage of 76% and method experts with a percentage of 81.4%, both of which are in the feasible category. The effectiveness was tested using a pretest–posttest design on 24 eighth grade students. The instrument used in measuring amotivation was a questionnaire, while collaboration was measured with an observation sheet supported by a questionnaire. The normality test showed that the motivation data were normally distributed so they were analyzed using the Paired Sample t-test, while the collaboration data were not normally distributed so they were analyzed using the Wilcoxon Signed-Rank Test. The test results showed a significant difference between the pretest and posttest scores on both variables (Sig. 0.000 < 0.05), which indicated an increase in student motivation and collaboration after the application of the method. The observation results showed a score of 100% which indicated that the Interactive media-based Benteng-bentengan method could improve student collaboration in social studies learning. Based on these results, the Interactive media-based Benteng-bentengan method was declared feasible, practical, and effective in improving student motivation and collaboration in social studies learning.